Technology Adoption and Nanostore Performance Enhancement in Honduras: A Humanitarian Engineering Perspective - Acevedo-Amaya, Mario Roberto; Ortega-Jimenez, Cesar H. (LACCEI, 2025)
Developing countries face several challenges in nanostores operations management (OM). The impact of adopting new information and communication technologies (ICT) on the performance of nanostores (R) is currently unclear. Therefore, an exploratory study was conducted on 616 nanostores located in 15 departments of Honduras. This study utilized context analysis and a multiple linear regression model to determine how much the independent variables (ICT) and operational management (OM) explain performance (R). The findings indicate a low rate of technology adoption among nanostores, primarily due to issues related to cost, digital literacy, access to technology, and the country’s infrastructure. Nevertheless, at least 30% of these businesses have incorporated technology. Finally, the results show that when nanostores use technology in operations management, their performance improves by 7%. These findings underscore the relevance of the Humanitarian Engineering in Latin America (HELA) approach, which advocates for context-sensitive technological solutions to enhance equity, resilience, and sustainable development in vulnerable communities. Additionally, the study emphasizes the importance of integrating contextually adapted technological solutions, fostering collaborative processes with distributor companies, and continuously improving management capabilities as essential strategies for enhancing operational performance, sustainability, and competitiveness in vulnerable contexts. As a future research direction, a second phase of data collection extending beyond Honduras to include Colombia and Peru is proposed. This will allow for cross-national comparisons and provide a deeper analysis of the region, contributing to HELA’s mission of promoting context-sensitive innovation and understanding how micro-entrepreneurs in Latin America can leverage technology and quality management for inclusive growth.